A telemedicine tool framework for lung sounds classification using ensemble classifier algorithms - Jaber M.M.; Abd S.K.; Shakeel P.M.; Burhanuddin M.A.; Mohammed M.A.; Yussof S. (Elsevier B.V., 2023)
Adaptive boosting; Biological organs; Decision trees; Pathology; Random forests; Ada boost classifiers; Boosting classifiers; Classification accuracy; Ensemble classifiers; Gradient boosting; Information exchanges; Random forest algorithm; Respiratory pathology; Telemedicine